Children with Down`s syndrome motor disturbance at age of 0 to 3-own cases analysis taking additional factors burdening the development into consideretion - Szymańska, Elżbieta; Bońkowska, Zofia (European Journal of Clinical and Experimental Medicine, 2005)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The aim of this work was to evaluate the children with Down syndrom. They were observed in their first three years of life in the Rehabilitation Centre of Children with Disabilities. All patients were treated with polimorphic stimualtion of psychomotor development. The examination included 40 kids with trisomy 21 and 19 of which were addtionally limited by innate organic heart disease or other risk factors. Children were evaluated in 2 months space. The age in which children gained the successive stage of development was registered (head conrtolling, supporting on forearms, turning, creeping, crawling on all fours, walking). It was show that all the examined patients were presenting the psychomotor development delay in the relation with development standards for healthy children. Patients with Down syndrom and additional risk factors (innate organic heart disease, epilepsy, OUN defekt) despite the rehabilitation had much slower development path than patients without additional limiting factors.